IDENTIFIKASI BAKTERI Staphylococcus aureus PADA PREPUTIUM DAN VAGINA KUDA (Equus caballus) (Identification of Staphylococcus aureus in Preputium and Vagina of Horses (Equus caballus)) - Yulina Rahmi; Darmawi Darmawi; Mahdi Abrar; Faisal Jamin; Fakhrurrazi Fakhrurrazi; Yudha Fahrimal (Universitas Syiah Kuala, 2015)
This research aims to identify the Staphylococcus aureus (S. aureus) bacteria from preputium and vagina of horses. Five swabs preputium and 5 swabs vagina samples from 3-9 years olds horse in the village of Bebangka, Gelelungi, Reloop, and Kelapeng, Pegasing Aceh Tengah District were used in this study. Preputium and vagina swabs of horses were dipped into reaction tube containing Nutrient Broth (NB). Staphylococcus aureus was identified on manitol salt agar (MSA). Separated colony colored bright yellow on the media were tested for Gram staining, hemolysis, catalase, and sugar test (glucose and manitol). The result showed that the isolates growth on MSA were colored bright yellow, Gram positive, β hemolisis, and catalase positive. The isolates fermented manitol and glucose. Isolates identified from horses preputium and vagina showed the characteristic of S. aureus. In conclusion S. aureus bacteria were positively identified from all of swabs samples, both in preputium and vagina of horses.Key words: Staphylococcus aureus, horse, preputium, vagina